Characterization of Potent ABCG2 Inhibitor Derived from Chromone: From the Mechanism of Inhibition to Human Extracellular Vesicles for Drug Delivery - Glaucio Valdameri; Diogo Henrique Kita; Julia de Paula Dutra; Diego Lima Gomes; Arun Kumar Tonduru; Thales Kronenberger; Bruno Gavinho; Izadora Volpato Rossi; Mariana Mazetto de Carvalho; Basile Pérès; Ingrid Fatima Zattoni; Fabiane Gomes de Moraes Rego; et al. (MDPI AG, 2023)
Inhibition of ABC transporters is a promising approach to overcome multidrug resistance in cancer. Herein, we report the characterization of a potent ABCG2 inhibitor, namely, chromone 4a (C4a). Molecular docking and in vitro assays using ABCG2 and P-glycoprotein (P-gp) expressing membrane vesicles of insect cells revealed that C4a interacts with both transporters, while showing selectivity toward ABCG2 using cell-based transport assays. C4a inhibited the ABCG2-mediated efflux of different substrates and molecular dynamic simulations demonstrated that C4a binds in the Ko143-binding pocket. Liposomes and extracellular vesicles (EVs) of Giardia intestinalis and human blood were used to successfully bypass the poor water solubility and delivery of C4a as assessed by inhibition of the ABCG2 function. Human blood EVs also promoted delivery of the well-known P-gp inhibitor, elacridar. Here, for the first time, we demonstrated the potential use of plasma circulating EVs for drug delivery of hydrophobic drugs targeting membrane proteins.